High-strength high-modulus aluminum-based silicon carbide foil and preparation method thereof
Through the two-particle distribution system and powder pretreatment and continuous extrusion process, the problems of high cost and poor uniformity in the preparation of aluminum-based silicon carbide foil are solved, and efficient and low-cost aluminum-based silicon carbide foil production are achieved, which significantly improves the production of aluminum-based silicon carbide foil The properties and uniformity of the material are achieved.
Patent Information
- Application Number
- CN202411338392.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
The existing aluminum-based silicon carbide foil preparation technology has the problems of high cost, low efficiency, and the difficulty in controlling the uniformity of silicon carbide particles during the smelting process, resulting in poor material performance.
The SiC mixed powder and high-purity Al powder with a two-particle distribution system are used for powder pretreatment and continuous extrusion processes to form automated continuous production, avoiding adverse reactions in the process of traditional casting, and improving the density and uniformity of the material. sex.
It significantly reduces production costs, improves the performance and structural uniformity of aluminum-based silicon carbide foil, reduces the cost by more than 60%, and significantly improves the mechanical properties.
Smart Images

Figure CN119220860A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum-based silicon carbide preparation, and in particular to a high-strength and high-modulus aluminum-based silicon carbide foil and a preparation method thereof. Background Art
[0002] Aluminum-based silicon carbide composite materials combine the characteristics of aluminum alloys such as high specific strength, good plastic processing properties, and low density, while taking into account the advantages of SiC particles such as high hardness and low thermal expansion coefficient. They are metal-based composite materials with excellent characteristics such as light weight and high performance.
[0003] Low volume fraction (15-25%) aluminum-based silicon carbide foil (0.2mm) can be used as the middle plate of folding screen mobile phones. It has the advantages of lightness, high thermal conductivity, and high strength. Compared with traditional middle plate materials such as aluminum-magnesium alloy, it has high specific stiffness and can be reduced by half in thickness; compared with steel-aluminum composite materials, it is lighter, with a weight reduction of more than 50%; compared with titanium alloy, it has high specific stiffness, is lighter and has good thermal conductivity. Therefore, it can well meet the development needs of folding screen mobile phones for thinness and lightness, and is also widely used in consumer electronic products such as tablets and computers.
[0004] There are three technical routes for the preparation of aluminum-based silicon carbide foil. The first is powder metallurgy billet + extrusion / hot rolling into plate and strip + multiple cold and warm rolling; the second is semi-solid stirring ingot + extrusion into plate and strip + multiple cold and warm rolling; the third is continuous casting and rolling plate and strip + multiple cold and warm rolling. The cost of powder metallurgy production is too high and the efficiency is too slow. Semi-solid stirring casting and continuous casting slabs cannot well control the uniformity of silicon carbide particles during the smelting process. At the same time, the casting and rolling temperature is high, and the brittle phase produced by the interface reaction between silicon carbide and aluminum at high temperature is not good. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and high-modulus aluminum-based silicon carbide foil and a preparation method thereof, which adopts a dual particle size distribution system and a process of powder pretreatment plus powder continuous extrusion to form automated continuous production, thereby improving the yield of powder and ingots, greatly reducing the cost of producing aluminum-based carbonized composite material thin strips by traditional processes, with the cost reduced by more than 60%, and also avoiding the adverse reaction at the interface of silicon carbide and aluminum liquid during the traditional casting process into billets, thereby greatly improving the performance and organizational uniformity of the aluminum-based composite material foil.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a high-strength and high-modulus aluminum-based silicon carbide foil material, which comprises 15-25% of SiC mixed powder and 75-85% of Al powder by mass percentage;
[0008] The SiC mixed powder includes α-SiC powder with a particle size of 15-30 μm and α-SiC powder with a particle size of 2-10 μm;
[0009] The difference in particle size between the two sizes of α-SiC powder is ≤28μm.
[0010] Furthermore, on the basis of the above technical solution, the mass ratio of the α-SiC powder with a particle size of 15-30 μm to the α-SiC powder with a particle size of 2-10 μm is 1:(2-3).
[0011] Further, on the basis of the above technical solution, the Al powder is a spherical Al powder with a particle size of 20-40 μm and a purity of more than 99%;
[0012] The difference between the particle size of the Al powder and the particle size of the α-SiC powder with a particle size of 15-30 μm is ≤10 μm.
[0013] The present invention also provides a method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil as described above, comprising the following steps:
[0014] S1: performing powder pretreatment on Al powder and SiC mixed powder to obtain pretreated mixed powder;
[0015] S2: continuously extruding the pretreated mixed powder to obtain a tape of the aluminum-based silicon carbide composite material;
[0016] S3: heating the coil of the aluminum-based silicon carbide composite material, uncoiling it, and rolling it multiple times to obtain a high-strength and high-modulus aluminum-based silicon carbide foil.
[0017] Further, based on the above technical solution, the powder pretreatment includes the following steps:
[0018] S11: drying and mixing the Al powder and the SiC mixed powder to obtain a composite powder;
[0019] S12: ball-milling the composite powder to obtain a mixed powder;
[0020] S13: vacuum degassing the mixed powder to obtain a pretreated mixed powder.
[0021] Further, based on the above technical solution, in step S11, the drying conditions include:
[0022] The drying temperature is 30-50℃ and the drying time is 4-6h;
[0023] And / or, in step S11, the mixing includes:
[0024] Use a three-dimensional mixer to preliminarily mix the Al powder and SiC mixed powder. The powder capacity needs to account for 70-80% of the mixer capacity. The rotation speed is 40-50rpm and the mixing time is 2-6h.
[0025] Further, based on the above technical solution, in step S12, the ball milling includes: sequentially using Si3N4 ceramic balls are used to mix the composite powders by high-energy ball milling on a planetary ball mill.
[0026] Wherein, the mass ratio of Si3N4 ceramic ball to composite powder is (3-6):1;
[0027] The process control agent is 1.5-2% stearic acid;
[0028] The ball milling speed is 250-350 r / min, and the ball milling time refers to using ceramic balls of different diameters in sequence, and the total ball milling time is 5-12 h.
[0029] Further, on the basis of the above technical solution, in step S13, the vacuum degassing is to vacuum degas the mixed powder in a vacuum degasser;
[0030] Among them, the working pressure of the vacuum degasser is 0.1-0.6Mpa.
[0031] Further, on the basis of the above technical solution, in step S2, the continuous extrusion is to feed the pretreated mixed powder into a continuous extruder for continuous extrusion;
[0032] Among them, the extrusion ratio of continuous extrusion is 5-8, the extrusion wheel speed is 8-12rpm / min, the extrusion temperature is 450-500℃, and the extrusion wheel speed is 10-20rpm;
[0033] And / or, the thickness of the coil of the aluminum-based silicon carbide composite material is 3-5 mm, and the coiling temperature is 250-350°C.
[0034] Further, based on the above technical solution, step S3 specifically includes the following steps:
[0035] The 3-5 mm aluminum-based silicon carbide coil obtained by continuous extrusion is heated to 350-400°C, then unrolled for rolling, with a reduction of 10-20% per pass, and the intermediate temperature during each rolling process is 350-400°C, and the heat preservation is 1-2 hours. After repeated multiple times, annealing is performed to obtain high-strength and high-modulus aluminum-based silicon carbide foil;
[0036] The annealing process includes: firstly heating the temperature to 500-550°C and keeping the temperature for 1-1.5 hours, then cooling the temperature to 150-200°C and keeping the temperature for 5-6 hours;
[0037] The thickness of the high-strength and high-modulus aluminum-based silicon carbide foil is 0.1-0.2 mm.
[0038] The present invention provides a high-strength and high-modulus aluminum-based silicon carbide foil and a preparation method thereof, and the beneficial effects are as follows:
[0039] 1. The present invention adopts a dual particle size distribution system, including a SiC mixed powder composed of α-SiC powder with a particle size of 15-30 μm and α-SiC powder with a particle size of 2-10 μm. Among them, the α-SiC powder with a particle size in the range of 15-30 μm, these larger particles of silicon carbide powder not only provide good structural support and strength foundation, but also promote the skeleton formation of the mixed powder in the subsequent processing process; and the α-SiC powder with a particle size of only 2-10 μm, these tiny particles can effectively fill the gaps between large particles, significantly reduce the porosity, and improve the overall density and uniformity.
[0040] 2. The present invention forms automated continuous production through the process of powder pretreatment and continuous powder extrusion, improves the yield of powder and ingots, greatly reduces the cost of producing aluminum-based carbonized composite material thin strips by traditional processes, and reduces the cost by more than 60%. It also avoids the adverse reaction between silicon carbide and aluminum liquid interface in the traditional casting process into billets, greatly improving the performance and organizational uniformity of aluminum-based composite material foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is an electron microscope scanning image of the aluminum-based silicon carbide foil provided in Example 1 of the present invention;
[0043] Figure 2 A schematic diagram of the working principle of continuous extrusion of particles provided by the present invention;
[0044] Icons: 1. Extrusion wheel; 2. Plug; 3. Extrusion die; 4. Extrusion cylinder; 5. Groove sealing block; 6. Feeding wheel; 7. Vacuum storage chamber; 8. Thin plate. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0046] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0047] According to a first aspect of the present invention, there is provided a high-strength and high-modulus aluminum-based silicon carbide foil material, comprising, by mass percentage, 15-25% (e.g., 17%, 20%, 23%, etc.) of SiC mixed powder and 75-85% (e.g., 78%, 81%, 83%, etc.) of Al powder;
[0048] The SiC mixed powder includes α-SiC powder with a particle size of 15-30 μm (such as 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, etc.) and α-SiC powder with a particle size of 2-10 μm (such as 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, etc.);
[0049] The difference in particle size between the two sizes of α-SiC powder is ≤28μm (such as 27μm, 26μm, 25μm, 20μm, etc.).
[0050] Specifically, the present invention adopts a dual particle size distribution system, including a SiC mixed powder composed of α-SiC powder with a particle size of 15-30μm and α-SiC powder with a particle size of 2-10μm. Among them, the α-SiC powder with a particle size in the range of 15-30μm, these larger particles of silicon carbide powder not only provide good structural support and strength foundation, but also promote the skeleton formation of the mixed powder in the subsequent processing process; and the α-SiC powder with a particle size of only 2-10μm, these tiny particles can effectively fill the gaps between large particles, significantly reduce the porosity, and improve the overall density and uniformity.
[0051] In the process of preparing SiC mixed powder, a key factor is that the difference in particle size between two different α-SiC powders needs to be strictly controlled within a certain range. When the difference in particle size exceeds 28μm, a series of adverse effects will occur:
[0052] First, too large a difference in particle size will significantly reduce the uniformity of the two sizes of α-SiC powder during the mixing process. The size gap between large particles and small particles makes it difficult to achieve an ideal uniform distribution state when mixing, and it is easy to have large particles densely distributed and small particles sparsely distributed in local areas, or vice versa. This uneven mixing state will not only increase the difficulty of subsequent processing, but also have an adverse effect on the microstructure of the final product;
[0053] Secondly, the inhomogeneity of the mixed powder will be directly transferred to the subsequent aluminum-based silicon carbide foil preparation process. In the subsequent continuous extrusion process, the inhomogeneous mixed powder will lead to the inhomogeneity of the internal structure of the foil, forming defects such as pores and cracks. These defects will reduce the mechanical properties of the foil.
[0054] Furthermore, the double-size silicon carbide powder is mixed with an appropriate amount of high-purity aluminum powder. The addition of aluminum powder not only improves the sintering performance of the mixture and promotes the bonding between SiC particles during high-temperature treatment, but also through its unique phase change behavior (such as thermite reaction), it may generate additional strengthening phases or improve interface bonding, further enhancing the organizational density and uniformity of the composite powder.
[0055] The synergistic effect of this dual-particle size mixing strategy and aluminum powder makes the final SiC / Al composite powder show unprecedented advantages in microstructure. Its organization is not only denser, reducing the performance degradation caused by porosity, but also ensures the uniformity of component distribution and avoids local stress concentration.
[0056] As an optional embodiment of the present invention, the mass ratio of the α-SiC powder with a particle size of 15-30 μm to the α-SiC powder with a particle size of 2-10 μm is 1:(2-3) (for example, 1:2.2, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, etc.).
[0057] Specifically, the mass proportion of α-SiC powder with a particle size of 2-10μm is controlled to be 2-3 times that of α-SiC powder with a particle size of 15-30μm, because small-particle α-SiC powder tends to find a stable configuration to reduce the total energy during the mixing process due to its smaller size and higher surface energy. When their number is significantly greater than that of large-particle α-SiC powder, these small particles can more naturally surround the large particles to form a microscopic arrangement similar to a "satellite" structure. This arrangement not only helps to reduce the gaps between particles and increase the packing density of the mixed powder, but also promotes close contact between particles, creating favorable conditions for the subsequent sintering process. More importantly, the formation of this microstructure is of significant significance for improving the effect of SiC mixed powder on foil. During the continuous extrusion process, small-particle α-SiC powder can more effectively fill the gaps between large particles and form a more dense and uniform microstructure. At the same time, due to the formation of a strong bonding interface between small particles and large particles, this microstructure can significantly improve the mechanical properties of the foil.
[0058] In addition, the high proportion of small-particle α-SiC powder in the mixed powder also helps to optimize the sintering kinetics. Small particles have a higher specific surface area and a shorter diffusion path, so they can participate in the sintering reaction faster and promote material migration and rearrangement between particles. This helps to accelerate the sintering densification process and improve the sintering efficiency and yield rate of foil.
[0059] However, when the content of large-particle α-SiC powder is greater than or equal to that of small-particle α-SiC powder, the dispersion and freedom of small-particle α-SiC powder in the mixed system will be restricted. The large particles may be close to each other to form larger gaps, while the small particles may not be able to fully fill these gaps due to insufficient number, resulting in a decrease in the packing density of the SiC mixed powder and an increase in porosity.
[0060] Secondly, this ratio change will also affect the sintering behavior of the mixed powder. During the sintering process, the contact area between large particles is relatively large, but due to the insufficient number of small particles, the sintering neck between them is difficult to form or expand effectively. This will lead to the obstruction of the sintering kinetics and the reduction of the sintering rate, and it is also not conducive to the formation of a dense microstructure. In addition, the direct contact between large particles may also induce stress concentration, increasing the risk of crack formation during sintering.
[0061] Furthermore, from the perspective of foil performance, a high proportion of large particles will weaken the contribution of small particles in enhancing the mechanical properties of the material. The presence of small particles can refine the grains, increase the interface bonding strength and improve the fracture toughness of the material. However, when large particles become dominant, these beneficial effects will be weakened or even offset. Key performance indicators such as the tensile strength, flexural strength and fracture toughness of the foil may therefore decline.
[0062] As an optional embodiment of the present invention, the Al powder is a spherical Al powder with a particle size of 20-40 μm (such as 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, etc.) and a purity of more than 99%;
[0063] The difference between the particle size of Al powder and the particle size of α-SiC powder with a particle size of 15-30 μm is ≤10 μm (such as 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, etc.).
[0064] Specifically, the difference between the particle size of Al powder and the particle size of α-SiC powder with a particle size of 15-30 μm is controlled to be ≤10 μm. The reasons are as follows:
[0065] 1) Promote uniform mixing: When the particle size of Al powder is similar to that of the larger α-SiC powder (15-30μm), the two are more likely to achieve a uniform distribution during the mixing process. The smaller particle size difference reduces the size gap between particles, making the mixing process smoother and helping to avoid particle agglomeration or sparseness in local areas;
[0066] 2) Optimize sintering dynamics: During the sintering process, the contact area and diffusion rate between particles are key factors affecting the sintering rate and densification degree. When the particle sizes of Al powder and α-SiC powder are similar, the contact area between them is relatively large, which is conducive to the diffusion and migration of atoms or ions. This accelerates the formation and growth of sintering necks, promotes the bonding between particles and the filling of pores, thereby improving the density and strength of the sintered body;
[0067] 3) Reduce stress concentration: If the particle size of Al powder is much smaller or larger than that of α-SiC powder, then during the sintering process, greater stress may be generated at the interface due to the difference in thermal expansion coefficient and shrinkage rate. This stress concentration may cause defects such as cracks or deformation in the sintered body. When the particle sizes of the two are similar, this stress difference can be reduced, the risk of crack formation can be reduced, and the overall performance of the sintered body can be improved;
[0068] 4) Improved interface bonding: Good interface bonding is the key to ensuring the performance of composite materials. When the particle sizes of Al powder and α-SiC powder are similar, the interface between them is smoother and more continuous, which is conducive to forming a strong interface bonding. This bonding improves the mechanical properties of the sintered body.
[0069] According to a second aspect of the present invention, there is provided a method for preparing a high-strength and high-modulus aluminum-based silicon carbide foil, comprising the following steps:
[0070] S1: performing powder pretreatment on Al powder and SiC mixed powder to obtain pretreated mixed powder;
[0071] S2: continuously extruding the pretreated mixed powder to obtain a tape of the aluminum-based silicon carbide composite material;
[0072] S3: heating the coil of the aluminum-based silicon carbide composite material, uncoiling it, and rolling it multiple times to obtain a high-strength and high-modulus aluminum-based silicon carbide foil.
[0073] Specifically, the present invention forms automated continuous production through the process of powder pretreatment and continuous powder extrusion, improves the yield of powder and ingots, greatly reduces the cost of producing aluminum-based carbonized composite material thin strips by traditional processes, and reduces the cost by more than 60%. It also avoids the adverse reaction at the interface between silicon carbide and aluminum liquid during the traditional casting process into billets, greatly improving the performance and organizational uniformity of aluminum-based composite material foil.
[0074] As an optional embodiment of the present invention, the powder pretreatment comprises the following steps:
[0075] S11: drying and mixing the Al powder and the SiC mixed powder to obtain a composite powder;
[0076] S12: ball-milling the composite powder to obtain a mixed powder;
[0077] S13: vacuum degassing the mixed powder to obtain a pretreated mixed powder.
[0078] As an optional embodiment of the present invention, in step S11, the drying conditions include:
[0079] The drying temperature is 30-50℃ and the drying time is 4-6h;
[0080] And / or, in step S11, the mixing includes:
[0081] Use a three-dimensional mixer to preliminarily mix the Al powder and SiC mixed powder. The powder capacity needs to account for 70-80% of the mixer capacity. The rotation speed is 40-50rpm and the mixing time is 2-6h.
[0082] As an optional embodiment of the present invention, in step S12, the ball milling includes: sequentially using Si3N4 ceramic balls are used to mix the composite powders by high-energy ball milling on a planetary ball mill.
[0083] Wherein, the mass ratio of Si3N4 ceramic ball to composite powder is (3-6):1;
[0084] The process control agent is 1.5-2% stearic acid;
[0085] The ball milling speed is 250-350 r / min, and the ball milling time refers to the total time of ball milling using ceramic balls of different diameters in sequence, which is 5-12 hours.
[0086] Specifically, ball milling is used in the early stage Ceramic balls can more effectively enter the tiny gaps between powder particles, and through high-frequency impact and shearing, the powder particles are initially refined. As the ball milling progresses, the powder particles have been initially refined, and at this time, ceramic balls with slightly larger diameters are used. While maintaining a certain refining effect, the impact force on the powder can be increased, which helps to further refine the particles. Ceramic balls with larger diameters can accumulate more energy during the ball milling process and release it during impact. This energy release helps to promote the crushing and reorganization of powder particles. In the later stage of ball milling, the powder particles are already relatively fine, and ceramic balls with larger diameters are used at this time. The distribution state of particles can be optimized and the agglomeration and voids between particles can be reduced; the impact of large balls helps the close contact and bonding between powder particles and promotes densification during the sintering process.
[0087] As an optional embodiment of the present invention, in step S13, the vacuum degassing is to vacuum degas the mixed powder in a vacuum degasser;
[0088] Among them, the working pressure of the vacuum degasser is 0.1-0.6Mpa.
[0089] As an optional embodiment of the present invention, in step S2, the continuous extrusion is to feed the pretreated mixed powder into a continuous extruder for continuous extrusion;
[0090] Among them, the extrusion ratio of continuous extrusion is 5-8, the extrusion wheel speed is 8-12rpm / min, the extrusion temperature is 450-500℃, and the extrusion wheel speed is 10-20rpm;
[0091] And / or, the thickness of the coil of the aluminum-based silicon carbide composite material is 3-5 mm, and the coiling temperature is 250-350°C.
[0092] Specifically, Figure 2As shown, the process in the continuous extruder is as follows: the mixed powder after vacuum degassing is added into the vacuum storage chamber 7 of the continuous extruder, the powder enters the feeding wheel 6 under the action of gravity, and then is transferred to the extrusion wheel 1 for extrusion through the feeding wheel 6, the powder becomes molten under the strong shear stress of the extrusion wheel 1 and the slot sealing block 5, the melt passes through the blocking of the plug 2 and enters the extrusion die 3 during the extrusion process, and then is extruded through the extrusion die 3 and the extrusion barrel 4, and is formed into a continuous 3-5mm thick thin plate 8 from the outlet of the extrusion die 3, and finally the thin plate 8 coming out of the die is wound by a constant tension winding device, and the winding temperature is 250-350°C, and finally a coil of aluminum-based silicon carbide composite material is obtained.
[0093] As an optional implementation of the present invention, step S3 specifically includes the following steps:
[0094] The 3-5 mm aluminum-based silicon carbide coil obtained by continuous extrusion is heated to 350-400°C, then unrolled for rolling, with a reduction of 10-20% per pass, and the intermediate temperature during each rolling process is 350-400°C, and the heat preservation is 1-2 hours. After repeated multiple times, annealing is performed to obtain high-strength and high-modulus aluminum-based silicon carbide foil;
[0095] The annealing process includes: firstly heating the temperature to 500-550°C and keeping the temperature for 1-1.5 hours, then cooling the temperature to 150-200°C and keeping the temperature for 5-6 hours;
[0096] The thickness of the high-strength and high-modulus aluminum-based silicon carbide foil is 0.1-0.2 mm (such as 0.12 mm, 0.14 mm, 0.16 mm, 0.18 mm, etc.).
[0097] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0098] Example 1
[0099] (1): 75% by mass of spherical Al powder (with an average particle size of 30 μm and a purity of 99.9%) and 25% by mass of SiC mixed powder were dried at a temperature of 40° C. for 5 h;
[0100] The SiC mixed powder includes α-SiC powder (purity of 99%) with an average particle size of 20 μm and α-SiC powder (purity of 99%) with an average particle size of 5 μm;
[0101] The mass ratio of α-SiC powder with an average particle size of 20 μm to α-SiC powder with an average particle size of 5 μm is 1:2;
[0102] The Al powder and SiC mixed powder were preliminarily mixed using a three-dimensional mixer, with the powder capacity accounting for 75% of the mixer capacity, the rotation speed being 45 rpm, and the mixing time being 4 hours to obtain composite powder.
[0103] (2): Use diameters of Si3N4 ceramic balls are used to mix the composite powders by high-energy ball milling on a planetary ball mill.
[0104] Among them, the mass ratio of Si3N4 ceramic balls to composite powder is 4:1; the process control agent is 1.8% stearic acid; the ball milling speed is 300r / min, and the ball milling time is 9h.
[0105] (3): The mixed powder is vacuum degassed in a vacuum degasser, and the working pressure of the vacuum degasser is 0.2 MPa;
[0106] The mixed powder after vacuum degassing is added to the vacuum storage chamber 7 of the continuous extruder. The powder enters the feeding wheel 6 under the action of gravity, and then is transferred to the extrusion wheel 1 for extrusion through the feeding wheel 6. The powder becomes a molten state under the strong shear stress of the extrusion wheel 1 and the groove sealing block 5. During the extrusion process, the melt passes through the blocking of the plug 2 and enters the extrusion die 3, and then is extruded through the extrusion die 3 and the extrusion cylinder 4. It is formed into a continuous 4mm thick thin plate 8 from the outlet of the extrusion die 3, wherein the extrusion ratio of the continuous extrusion is 6, the extrusion wheel speed is 10rpm / min, the extrusion temperature is 470℃, and the extrusion wheel speed is 15rpm; finally, the thin plate coming out of the die is rolled up by a constant tension winding device, and the winding temperature is 300℃, and finally a coil of aluminum-based silicon carbide composite material is obtained.
[0107] (4): The 4 mm aluminum-based silicon carbide coil obtained by continuous extrusion is heated to 370°C, then unrolled and rolled, with a reduction of 15% in each pass and an intermediate temperature of 370°C in each rolling process. The heat is kept for 1 hour. After repeating 4 times, annealing is performed, first by heating to 535°C for 1 hour, then cooling to 175°C for 6 hours, to obtain a high-strength and high-modulus aluminum-based silicon carbide foil with a thickness of 0.1 mm.
[0108] like Figure 1 As shown, the aluminum-based silicon carbide foil prepared in this embodiment has good structural uniformity and the particle sizes are basically the same.
[0109] Example 2
[0110] (1): 85% by mass of spherical Al powder (average particle size of 20 μm, purity of 99.9%) and 15% by mass of SiC mixed powder were dried at 30° C. for 6 h;
[0111] The SiC mixed powder includes α-SiC powder (purity of 99%) with an average particle size of 15 μm and α-SiC powder (purity of 99%) with an average particle size of 2 μm;
[0112] The mass ratio of α-SiC powder with an average particle size of 15 μm to α-SiC powder with an average particle size of 2 μm is 1:3;
[0113] Use a three-dimensional mixer to preliminarily mix the Al powder and SiC mixed powder. The powder capacity needs to account for 70% of the mixer capacity. The rotation speed is 40 rpm and the mixing time is 6 hours to obtain composite powder.
[0114] (2): Use diameters of Si3N4 ceramic balls are used to mix the composite powders by high-energy ball milling on a planetary ball mill.
[0115] The mass ratio of Si3N4 ceramic balls to composite powder is 3:1; the process control agent is 1.5% stearic acid; the ball milling speed is 250 r / min, and the ball milling time is 12 h.
[0116] (3): vacuum degassing the mixed powder in a vacuum degasser;
[0117] Among them, the working pressure of the vacuum degasser is 0.1Mpa;
[0118] The mixed powder after vacuum degassing is added to the vacuum storage chamber 7 of the continuous extruder. The powder enters the feeding wheel 6 under the action of gravity, and then is transferred to the extrusion wheel 1 for extrusion through the feeding wheel 6. The powder becomes a molten state under the strong shear stress of the extrusion wheel 1 and the groove sealing block 5. During the extrusion process, the melt passes through the blocking of the plug 2 and enters the extrusion die 3, and then is extruded through the extrusion die 3 and the extrusion cylinder 4. It is formed into a continuous 3mm thick thin plate 8 from the outlet of the extrusion die 3, wherein the extrusion ratio of the continuous extrusion is 5, the extrusion wheel speed is 8rpm / min, the extrusion temperature is 450℃, and the extrusion wheel speed is 10rpm; finally, the thin plate coming out of the die is rolled up by a constant tension winding device, and the winding temperature is 250℃, and finally a coil of aluminum-based silicon carbide composite material is obtained.
[0119] (4): The 3 mm aluminum-based silicon carbide coil obtained by continuous extrusion is heated to 350°C, then unrolled and rolled, with a reduction of 10% in each pass and an intermediate temperature of 350°C in each rolling process. The heat is maintained for 1 hour. After repeating 5 times, annealing is performed, first by heating to 500°C and maintaining for 1.5 hours, then cooling to 150°C and maintaining for 5 hours, to obtain a high-strength and high-modulus aluminum-based silicon carbide foil with a thickness of 0.15 mm.
[0120] Example 3
[0121] (1): 80% by mass of spherical Al powder (average particle size of 40 μm, purity of 99.9%) and 20% by mass of SiC mixed powder were dried at 50° C. for 4 h;
[0122] The SiC mixed powder includes α-SiC powder (purity of 99%) with an average particle size of 30 μm and α-SiC powder (purity of 99%) with an average particle size of 10 μm;
[0123] The mass ratio of α-SiC powder with an average particle size of 30 μm to α-SiC powder with an average particle size of 10 μm is 1:2.5;
[0124] Use a three-dimensional mixer to preliminarily mix the Al powder and SiC mixed powder. The powder capacity needs to account for 80% of the mixer capacity. The rotation speed is 50 rpm and the mixing time is 2 hours to obtain composite powder.
[0125] (2): Use diameters of Si3N4 ceramic balls are used to mix the composite powders by high-energy ball milling on a planetary ball mill.
[0126] The mass ratio of Si3N4 ceramic balls to composite powder is 6:1; the process control agent is 2% stearic acid; the ball milling speed is 350 r / min, and the ball milling time is 5 h.
[0127] (3): vacuum degassing the mixed powder in a vacuum degasser;
[0128] Among them, the working pressure of the vacuum degasser is 0.3Mpa;
[0129] The mixed powder after vacuum degassing is added to the vacuum storage chamber 7 of the continuous extruder. The powder enters the feeding wheel 6 under the action of gravity, and then is transferred to the extrusion wheel 1 for extrusion through the feeding wheel 6. The powder becomes a molten state under the strong shear stress of the extrusion wheel 1 and the groove sealing block 5. During the extrusion process, the melt passes through the blocking of the plug 2 and enters the extrusion die 3, and then is extruded through the extrusion die 3 and the extrusion cylinder 4. It is formed into a continuous 5mm thick thin plate 8 from the outlet of the extrusion die 3, wherein the extrusion ratio of the continuous extrusion is 8, the extrusion wheel speed is 12rpm / min, the extrusion temperature is 500℃, and the extrusion wheel speed is 20rpm; finally, the thin plate coming out of the die is rolled up by a constant tension winding device, and the winding temperature is 350℃, and finally a coil of aluminum-based silicon carbide composite material is obtained.
[0130] (4): The 5 mm aluminum-based silicon carbide coil obtained by continuous extrusion is heated to 400°C, then unrolled and rolled, with a reduction of 20% in each pass and an intermediate temperature of 400°C in each rolling process. The heat is kept for 2 hours. After repeating 3 times, annealing is performed, first by heating to 550°C and keeping it for 1.5 hours, then cooling to 200°C and keeping it for 6 hours, to obtain a high-strength and high-modulus aluminum-based silicon carbide foil with a thickness of 0.2 mm.
[0131] Comparative Example 1
[0132] The main difference between this comparative example and Example 1 is that no SiC mixed powder is added, that is, the raw material is only spherical Al powder (with an average particle size of 30 μm and a purity of 99.9%), and the remaining steps and technical parameters are the same as those of Example 1.
[0133] Comparative Example 2
[0134] The main difference between this comparative example and Example 1 is that only α-SiC powder with an average particle size of 20 μm is added, and the remaining steps and technical parameters are the same as those of Example 1.
[0135] Comparative Example 3
[0136] The main difference between this comparative example and Example 1 is that only α-SiC powder with an average particle size of 5 μm is added, and the remaining steps and technical parameters are the same as those of Example 1.
[0137] Comparative Example 4
[0138] The main difference between this comparative example and Example 1 is that the difference in particle size between the two sizes of α-SiC powder is 30 μm, that is, α-SiC powder with an average particle size of 35 μm and α-SiC powder with an average particle size of 5 μm are added, and the remaining steps and technical parameters are the same as those in Example 1.
[0139] Comparative Example 5
[0140] The main difference between this comparative example and Example 1 is that the mass ratio of α-SiC powder with an average particle size of 20 μm to α-SiC powder with an average particle size of 5 μm is 2:1, and the remaining steps and technical parameters are the same as those in Example 1.
[0141] Comparative Example 6
[0142] The main difference between this comparative example and Example 1 is that the particle size difference between the Al powder (40 μm) and the α-SiC powder with an average particle size of 20 μm is 20 μm. The remaining steps and technical parameters are the same as those in Example 1.
[0143] The specific test method is as follows:
[0144] Tensile test: The tensile test specimens of composite materials are processed according to the standard of GB / T228-2010 "Room Temperature Tensile Test of Metallic Materials", and the carbon fiber is ensured to be located in the center of the tensile sheet.
[0145] The tensile properties of the samples were tested using a DNS100 universal testing machine at a tensile speed of 1.2 mm / min.
[0146] Fracture toughness refers to GB / T 4161-2007 "Test method for plane strain fracture toughness KIC of metallic materials".
[0147] The elastic modulus refers to "GB / T 3354-2018 Determination of elastic modulus of metal materials at room temperature".
[0148] Table 1 is a comparison table of the mechanical properties of the aluminum-based silicon carbide foils prepared in Examples 1-3 and Comparative Examples 1-6, as shown below:
[0149] Table 1
[0150]
[0151] According to Table 1, compared with Example 1, the mechanical properties of the aluminum foil prepared in Comparative Example 1 are much lower than those in Example 1 due to the absence of the addition of SiC mixed powder.
[0152] According to Table 1, compared with Example 1, Comparative Example 2 adds only α-SiC powder with an average particle size of 20 μm, and cannot utilize the difference in particle size to improve the uniformity and density of the aluminum-based silicon carbide foil structure, so its mechanical properties are lower than those of Example 1.
[0153] According to Table 1, compared with Example 1, since only α-SiC powder with an average particle size of 5 μm is added in Comparative Example 3, the uniformity and density of the aluminum-based silicon carbide foil structure cannot be improved by utilizing the difference in particle size, resulting in its mechanical properties being lower than those in Example 1.
[0154] According to Table 1, compared with Example 1, since the difference in particle size between the two sizes of α-SiC powder is 30 μm, the difference is too large, which significantly reduces the uniformity of the two sizes of α-SiC powder during the mixing process, resulting in the mechanical properties of the prepared aluminum foil being less than those in Example 1.
[0155] According to Table 1, compared with Example 1, since the mass ratio of α-SiC powder with an average particle size of 20 μm to α-SiC powder with an average particle size of 5 μm is 2:1, the large-sized α-SiC powder accounts for too much, which reduces the packing density of the SiC mixed powder and increases the porosity, resulting in the mechanical properties of the prepared aluminum foil being less than those in Example 1.
[0156] According to Table 1, compared with Example 1, since the particle size difference between the Al powder and the α-SiC powder with an average particle size of 20 μm is 20 μm, the Al powder and the α-SiC powder generate greater stress at the interface due to the difference in thermal expansion coefficient and shrinkage rate during the sintering process, resulting in the mechanical properties of the prepared aluminum foil being less than those in Example 1.
[0157] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength and high-modulus aluminum-based silicon carbide foil, characterized in that: The invention comprises 15-25% SiC mixed powder and 75-85% Al powder by mass percentage; The SiC mixed powder includes α-SiC powder with a particle size of 15-30 μm and α-SiC powder with a particle size of 2-10 μm; The difference in particle size between the two sizes of α-SiC powder is ≤28μm.
2. The high-strength and high-modulus aluminum-based silicon carbide foil according to claim 1, characterized in that: The mass ratio of the α-SiC powder with a particle size of 15-30 μm to the α-SiC powder with a particle size of 2-10 μm is 1:(2-3).
3. The high-strength and high-modulus aluminum-based silicon carbide foil according to claim 1, characterized in that: The Al powder is a spherical Al powder with a particle size of 20-40 μm and a purity of more than 99%; The difference between the particle size of the Al powder and the particle size of the α-SiC powder with a particle size of 15-30 μm is ≤10 μm.
4. A method for preparing a high-strength and high-modulus aluminum-based silicon carbide foil as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1: performing powder pretreatment on Al powder and SiC mixed powder to obtain pretreated mixed powder; S2: continuously extruding the pretreated mixed powder to obtain a tape of the aluminum-based silicon carbide composite material; S3: heating the coil of the aluminum-based silicon carbide composite material, uncoiling it, and rolling it multiple times to obtain a high-strength and high-modulus aluminum-based silicon carbide foil.
5. The method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil according to claim 4, characterized in that: The powder pretreatment comprises the following steps: S11: drying and mixing the Al powder and the SiC mixed powder to obtain a composite powder; S12: ball-milling the composite powder to obtain a mixed powder; S13: vacuum degassing the mixed powder to obtain a pretreated mixed powder.
6. The method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil according to claim 5, characterized in that: In step S11, the drying conditions include: The drying temperature is 30-50℃ and the drying time is 4-6h; And / or, in step S11, the mixing includes: Use a three-dimensional mixer to preliminarily mix the Al powder and SiC mixed powder. The powder capacity needs to account for 70-80% of the mixer capacity. The rotation speed is 40-50rpm and the mixing time is 2-6h.
7. The method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil according to claim 5, characterized in that: In step S12, the ball milling includes: sequentially using Si3N4 ceramic balls are used to mix the composite powders by high-energy ball milling on a planetary ball mill. Wherein, the mass ratio of Si3N4 ceramic ball to composite powder is (3-6):1; The process control agent is 1.5-2% stearic acid; The ball milling speed is 250-350 r / min, and the ball milling time refers to using ceramic balls of different diameters in sequence, and the total ball milling time is 5-12 h.
8. The method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil according to claim 5, characterized in that: In step S13, the vacuum degassing is to vacuum degas the mixed powder in a vacuum degasser; Among them, the working pressure of the vacuum degasser is 0.1-0.6Mpa.
9. The method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil according to claim 4, characterized in that: In step S2, the continuous extrusion is to feed the pretreated mixed powder into a continuous extruder for continuous extrusion; Among them, the extrusion ratio of continuous extrusion is 5-8, the extrusion wheel speed is 8-12rpm / min, the extrusion temperature is 450-500℃, and the extrusion wheel speed is 10-20rpm; And / or, the thickness of the coil of the aluminum-based silicon carbide composite material is 3-5 mm, and the coiling temperature is 250-350°C.
10. The method for preparing the high-strength and high-modulus aluminum-based silicon carbide foil according to claim 4, characterized in that: Step S3 specifically includes the following steps: The 3-5 mm aluminum-based silicon carbide coil obtained by continuous extrusion is heated to 350-400°C, then unrolled for rolling, with a reduction of 10-20% per pass, and the intermediate temperature during each rolling process is 350-400°C, and the heat preservation is 1-2 hours. After repeated multiple times, annealing is performed to obtain high-strength and high-modulus aluminum-based silicon carbide foil; The annealing process includes: firstly heating the temperature to 500-550°C and keeping the temperature for 1-1.5 hours, then cooling the temperature to 150-200°C and keeping the temperature for 5-6 hours; The thickness of the high-strength and high-modulus aluminum-based silicon carbide foil is 0.1-0.2 mm.
